Model Kepemimpinan Lembaga PAUD kelas Menengah Berbasis Fullday School: Study Kasus di Pre-school Jogja Kids Park Yogyakarta - Sri Wahyuni (JECED : Journal of Early Childhood Education and Development, 2019)
School leadership has a fairly heavy duty and responsibility, the success of an educational institution is determined by how the principal performs his role. The full day school based PAUD institution leadership model in Pree-school Jogja kids park aims to find out why parents from the middle class community choose to send their children to a full day school based school, and to find out how the leadership model used in Pre-school Jogja kids park. This type of research forms descriptive using a qualitative approach. Data collection techniques using observation, interviews, and documentation. Data analysis used the Miles and Huberman model which included data presentation, data reduction, and drawing conclusions. The results of this study indicate that the Pre-school Jogja kids park uses a transformational leadership model (changing situations, changing what is usually done, talking about noble goals, having a reference to the values ??of freedom, justice, equality). The parents of the middle class are mostly active workers who spend a lot of time outside the home